Phenytoin induced oxidative stress in pre- and postnatal rat development - effect of vitamin E on selective biochemical variables - Navarová, Jana; Ujházy, Eduard; Dubovický, Michal; Mach, Mojmír (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2005)
A pre- and postnatal study was carried out to investigate the effect of high dose (500 mg/kg) of the natural antioxidant vitamin E (VIT E) on biochemical variables in the model of chronic intrauterine hypoxia. Chronic hypoxia was induced by administration of the anticonvulsant phenytoin (PHT) during pregnancy. Rats were orally treated with PHT (150 mg/kg) from day 7 to 18 of gestation and VIT E prior to PHT orally on the same days. The activity of the lysosomal enzyme N-acetyl-ss-D-glucosaminidase (NAGA) and the level of glutathione (GSH) were used as markers of tissue damage. In the prenatal study PHT-induced embryofoetal toxicity was associated with an increase in NAGA activity and decrease of GSH level in maternal serum and heart and with an increase in NAGA activity in the placenta. Administration of VIT E did not inhibit the above given changes. PHT increased the activity of NAGA and decreased the level of GSH in foetal organs (liver, lungs, brain). VIT E did not reverse these changes. In the postnatal study, we did not find any significant differences in NAGA activity in the organs of 1-day-old pups. An increase of liver GSH level was found in PHT and VIT E+PHT groups of pups and in the group VIT E+PHT in the lungs. In conclusion, supplementation with a high-dose of VIT E failed to protect maternal, foetal and new-born rat organs from PHT induced changes of selective biochemical variables.
Keywords: Anticonvulsants; Oxidative Stress; oxidační stres; Pregnancy; Acetylglucosaminidase; antikonvulziva; Vitamin E; Female; Phenytoin; novorozená zvířata; krysa rodu Rattus; Antioxidants; zvířata; potkani Wistar; Fetus; fenytoin; antioxidancia; plod; Animals, Newborn; ženské pohlaví; Rats, Wistar; acetylglukosaminidasa; těhotenství; Rats; Animals; vitamin E